"Nanorust"‐catalyzed Benign Oxidation of Amines for Selective Synthesis of Nitriles. Issue 1 (24th October 2014) - Jagadeesh, Rajenahally V.; Junge, Henrik; Beller, Matthias
Abstract Organic nitriles constitute key precursors and central intermediates in organic synthesis. In addition, nitriles represent a versatile motif found in numerous medicinally and biologically important compounds. Generally, these nitriles are synthesized by traditional cyanation procedures using toxic cyanides. Herein, we report the selective and environmentally benign oxidative conversion of primary amines for the synthesis of structurally diverse aromatic, aliphatic and heterocyclic nitriles using a reusable "nanorust" (nanoscale Fe2O3)‐based catalysts applying molecular oxygen.